Quark-hybrid matter in the cores of massive neutron stars - Orsaria, Milva Gabriela (2013)
Using a nonlocal extension of the SU(3) Nambu-Jona-Lasinio model, which reproduces several of the key features of quantum chromodynamics, we show that mixed phases of deconfined quarks and confined hadrons (quark-hybrid matter) may exist in the cores of neutron stars as massive as around 2.1M âŠ™. The radii of these objects are found to be in the canonical range of ∼12-13 km. According to our study, the transition to pure quark matter does not occur in stable neutron stars, but is shifted to neutron stars which are unstable against radial oscillations. The implications of our study for the recently discovered, massive neutron star PSR J1614-2230, whose gravitational mass is 1.97±0.04MâŠ™, are that this neutron star may contain an extended region of quark-hybrid matter at it center, but no pure quark matter.